The Influence of Third Party Fund to Net Profit Margin at PT. Bank Tabungan Negara (Persero) Tbk. (Period 2014-2020) - Hadi Purnomo; Rani Widianingsih (Peneliti.net, 2021)
The purpose of this study is to determine the development of third party funds and net profit margins and to determine how much influence third party funds have on net profit margins at PT. Bank Tabungan Negara (Persero) Tbk.The research method used is descriptive verification method with a quantitative approach. By using secondary data in the form of a statement of financial position and income statement obtained from the IDX. Data collection techniques using field studies and literature studies. The data were analyzed using the calculation of the development of third party funds and net profit margins, and analyzed using statistical analysis assisted by SPSS Statistics 22 for windows.The results of this study indicate that third party funds have a very low relationship to net profit margins. With the influence that third party funds do not affect the net profit margin much. The results of simple linear regression analysis have a negative effect which shows that the relationship between third party funds and net profit margins is not unidirectional. And when viewed at the level of significance, it has no significant effect. So it can be concluded that third party funds have a negative and no significant effect on net profit margins, meaning that if third party funds increase, it will not always affect net profit margins.